Meningkatkan Potensi Pemasaran Digital Untuk Mengangkat Profil UMKM Kopi Sidikalang Secara Global - Rizki Sitanggang; Lenti Susana Ginting; Aurora Elise Putriku; Merichy Telaumbanua; Elmina Ginting (GEMILANG: Jurnal Manajemen dan Akuntansi, 2024)
The rise of technology and ever-increasing business competition, digital marketing strategies play a vital role in shaping entrepreneurial success in the dynamic landscape of the digital era. This research was conducted to determine the marketing strategies carried out by MSMEs in facing competition in the digital era. The research method in this research uses qualitative methods and literature study. Literature study means collecting data by studying theories from different literature that are relevant to the research being conducted. The results of the research show that for the culinary, fashion, and tour and travel industries, they provide added value and differentiation in the products and services provided, while in terms of price, they apply competitive and competitive prices. In contrast to the trading industry, they mostly use competitive pricing strategies, apart from that they also have a target market that tends to focus on niche markets so that their products can be accepted by the market. In the trading industry, on the other hand, they are more likely to use pricing strategies to compete in the market and choose market niches to develop their target market.